Reviewer Acknowledgements and Editorial Highlights: Bridging Clinical Insights and Public Health Solutions - GHMJ (Global Health Management Journal), Volume 8, Number 2s, 2025 - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal), 2025)
This Special Edition of the GHMJ (Global Health Management Journal) presents six diverse studies that reflect the breadth of health challenges across Indonesia, addressed at the 1st Cirebon International Health Symposium (Vol.8, No.2s, 2025). From the clinical field, a study on head injury patients highlights the link between CT-scan midline shift and Glasgow Coma Scale outcomes, offering valuable insight for emergency care (Permana, Royyani, & Ladala, 2025). Complementing this, genetic research identifies ACE2 G8790A polymorphism as a potential risk factor for essential hypertension, emphasizing the importance of biomedical perspectives in understanding chronic disease (Husna, Nauphar, & Pratamawati, 2025). At the community level, investigations reveal key determinants of leprosy treatment success (Sari, Risman, & Affandi, 2025), highlight pediatric tuberculosis risk factors (Pratama, Nisaa, & Ruhyana, 2025), and expose contamination in refilled drinking water (Shonia, Fitriani, & Indrakusuma, 2025), each pointing to urgent public health and environmental concerns. Meanwhile, attention to medical education is seen in a study exploring how motivation shapes professional identity among medical students, reminding us that building strong health systems begins with cultivating future professionals (Mustopa, Permatasari, & Sulistiyana, 2025). Together, these contributions showcase the Journal’s commitment to advancing integrated knowledge in clinical practice, public health, and education. Link to download: https://publications.inschool.id/index.php/ghmj/issue/view/CIHES02s We extend our heartfelt appreciation to the reviewers who have played a crucial role in refining and enhancing these works. Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Ph.D. Journal Managers Suyitno, M.PHM Maretalinia, M.A, Ph.D. Reviewers Witri Pratiwi, M.Kes. (Universitas Swadaya Gunung Jati, Indonesia) Putu Erma Pradnyani, S.KM., M.Kes. (Universitas Pembangunan Nasional Veteran, Indonesia) Piti Anontapant, Ph.D (Cand.) (Ramkhamhaeng University, Thailand) drg. Theresia Puspitawati, M Kes. (Universitas Respati Yogyakarta, Indonesia) Vivi Meidianawaty, M.MedEd (Universitas Swadaya Gunung Jati, Indonesia) Supim Wongtongtair, Ph.D. (Srinakharinwirot University, Thailand) Eligible reviewers may be considered for future roles on our Editorial Board, and receive Exclusive Publishing Opportunity and the chance to publish Guest Editorial Papers at no cost. Simply register on our website and select the "Reviewer" option during sign-up.  Acceptance Rate   : 33 % Days to First Editorial Decision  : 18 days Days to accept  : 55 days   Published: 21 August 2025